Effect of Communication Effectiveness and Implementation Cyber Public Relations on Image Formation Politenik Negeri Semarang - Rara Ririn Budi Utaminingtyas; Taviyastuti - Taviyastuti; Nur - Rini; Rustono - Rustono; Fatchun - Hasyim (Politeknik Negeri Semarang, 2023)
Politeknik Negeri Semarang conducts online-based communication through web media types: www.polines.ac.id, twitter:@polinesofficial, facebook: Polines Official, instagram: PolinesOfficial, youtube: PolinesOfficial. Politeknik Negeri semarang applies Cyber Public Relations as a means of communication performance. Cyber public relations is an application of ICT (Information and Communication Technologies) tools for the purposes of Public Relations. The purpose of this study was to determine the effect of the effectiveness of communication and the application of cyber PR on the image formation of the Politeknik Negeri Semarang. The sample used in this study was 121 students, lecturers, education staff, as well as the general public outside the campus. Data collection using observation, and questionnaires with Differential Semantic scale. The result of the regression analysis is the value of F = 45,634 with Sig 0.000<0,05 . This means that the implementation of Cyber Public Relations and Communication Effectiveness simultaneously have a significant effect on the Image of Polines. The coefficient of determination is 0.691. This means that the application of Cyber PR and Communication Effectiveness has an effect on the imageof Polines by 69.1%, the remaining 30,9% is influenced by other variables not examined. The implementation of Cyber Public Relations through Online Publications, through the use social media partially has no significant effect on the image ofPolines.. The implementation of Cyber Public Relations through the Online Community Level partially has a significant effect on the image of Polines. Assessment of the Effectiveness of Cyber PR Communication through the Level of Information Capture (exposure) partially has a significant effect on the image of Polines. Assessment of Cyber PR Communication Effectiveness through the level of attention (attention),, through the level of understandingha (comprehensive), partially has no significant effect on the image of Polines.